OS TESOUROS DO MORRO DO CASTELO: OURO DOS JESUÍTAS NO IMAGINÁRIO DO RIO DE JANEIRO (Revista de História Regional, 2007)
The belief in treasures hidden under Castelo Hill has fascinated for centuries the people of Rio de Janeiro. Writers, engineers and historians were among those who believed that the Jesuits, before their expulsion by Pombal in 1759, had hidden incalculable riches in underground passages radiating from the Church and College built in the hill. This belief, reinforced by documents considered doubtful by many, lasted till the opening of the Avenida Rio Branco in 1905, when a gallery was found, confirming the existence of a network of tunnels under the mountain. One of the aims of this article is to follow the path of this belief and of the people who shared it, contrasting a daily life of poverty with the dreams of riches. It also examined the multiplicity of discourses and practices - religious, mythical, medical and urbanistic - having the Castelo Hill as their object of study, which were iniatilly mixed up and divergent afterwards, as the city birthplace, full of historical and religious significance, approached its destruction by razing. That happened in the nineteen-twenties, in the name of the need for ventilation and embellishment of the city, after a long and intense discussion.